Contextualizing post day-one childhood immunization in-take drop-off rate in Nigeria: An assessment of working mothers in Ibadan [version 2; peer review: 1 approved, 3 approved with reservations] - Olugbenga S. Falase; Folakemi A. Amodu; Olukemi K. Amodu; Taiwo H. Olajide; Mofeyisara O. Omobowale (Gates Open Research)
Background Contextualizing childhood immunization in the context of children of working mothers can boost coverage and completion interventions. This study examines how informal working mothers perceive post-day-one routine immunization, and vaccines not covered under the National Program on Immunization (NPI), immunization schedules, timing, and duration. Methods The study utilized a mixed methods approach, including in-depth interviews and semi-structured questionnaire to capture immunization experiences and assess the context of post-day one. The study was conducted in Ibadan, Nigeria and involved 1,044 quantitative and 73 qualitative samples of working nursing mothers. Data were analyzed using descriptive statistics, chi-square test for proportions, and t-test for means (p<0.05), while qualitative data were subjected to content and thematic analysis. Results The average age of mothers participating in this study was 31.39±6.52 years. The mean age of children of mothers recruited into this study is 19.26 ±16.14 months. Majority of these mothers (95%) are married. Around three-quarters of women in this population ensured immediate immunization for their infants after birth, but less than a third achieved the complete age-specific vaccination series due to livelihood related causes, long waiting time spent in conventional immunization clinic. Around 40% of interviewed mothers vaccinated their children up to the third DPT dose, and just over 30% achieved full vaccination. Many informal working mothers, have practice of adding 'supplements' to their children's immunization, driven by a lack of sufficient information about the vaccines. Some mothers also seemed unaware of these specialized vaccines. Conclusions Promoting complete immunization requires more than just raising awareness about childhood vaccinations but close and quick immunization service delivery is required. It is crucial for mothers to possess comprehensive knowledge about the mechanics and operation of immunization. Achieving this understanding could involve translating vaccine names and functions into indigenous terms, enhancing clarity and comprehension. Furthermore, a firm grasp of the immunization schedule significantly contributes to successful immunization completion.